The Impact of Coffee Market Reforms on Producer Prices and Price Transmission - Krivonos, Ekaterina (World Bank, Washington, D.C., 2013)
This paper evaluates the impact of coffee sector reforms during late 1980s and early 1990s on coffee growers in the main coffee producing countries. Earlier evidence suggests that the reforms increased the share of producer prices in the world price of coffee. This hypothesis is tested in the paper with the help of cointegration analysis, and the results show that in most countries the longterm producer price share has indeed increased substantially after the liberalization. Moreover, the results suggest that the reforms induced a closer cointegrating relationship between grower prices and world market prices. Finally, estimation of an error-correction model reveals that short-run transmission of price signals from the world market to domestic producers has improved, such that domestic prices adjust faster today to world price fluctuations than they did prior to the reforms. However, there is some evidence of asymmetries in the way positive and negative world price changes are transmitted to domestic markets.